ORIENTASI EKONOMI DALAM SISTEM PENGELOLAAN SAMPAH DOMESTIK TERPADU DI INDONESIA - Suprapto suprapto (Jurnal Rekayasa Lingkungan)
Environmental life cycle assessment on Integrated solid waste management hasdeveloped rapidly during the 1990s and has reached a certain level of harmonisation and standardisation. LCA has mainly been developed for analysing material products, but can also be applied to services, e.g. treatment of a particular amount of solid waste. This paper discusses some methodological issues which come into focus when LCAs are applied to solid waste management systems. The following issues are discussed. (1) Open-loop recycling allocation: besides taking care of a certain amount of solid waste, many treatment processes also provide additional functions, e.g. energy or materials which are recycled into other products. Two important questions which arise are if an allocation between the different functions should be made (and if so how), or if system boundaries shouldÂ be expanded to include several functions. (2) Multi-input allocation: in waste treatment processes, different materials and products are usually mixed. In many applications there is a need to allocate environmental interventions from the treatment processes to the different input materials. (3) Time: emissions from landfills will continue for a long time.An important issue to resolve is the length of time emissions from the landfill should be considered. Effective schemes need the flexibility to design, adapt and operate systems in ways which best meet current social, economic and environmental conditions. These are likely to change over time and vary by geography. The need for consistency in quality and quantity of recycled materials, compost or energy, the need to support a range of disposaloptions and the benefit of economies of scale, all suggest that integrated waste management should be organized on a large-scale, regional basis. Any scheme incorporating recycling, composting or waste-to-energy technologies must be market-orientated. There must be markets for products and energy.Keywords : municiple solid waste management, economic orientation of waste